2022
DOI: 10.15562/bmj.v11i3.3474
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pursed-lips breathing and diaphragm exercises on the quality of life of COPD patient assessed by six-minutes walk test

Abstract: Introduction: Chronic obstructive pulmonary disease (COPD) is a chronic inflammation that causes a variety of pulmonary and systemic disorders. Pursed-lip breathing and diaphragmatic breathing exercises are useful techniques for improving ventilation, reducing the degree of breathlessness, enhancing performance, and improving quality of life. The aim of this study was to determine the effect of pursed-lip breathing and diaphragmatic breathing exercise on the value of the 6-min walk test and to improve quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Pada kelima pasien mengalami penurunan frekuensi napas setelah diberikan intervensi kombinasi PLB dan DBE. Hal tersebut sejalan dengan penelitian Mulyadi et al (2022) menunjukkan intervensi PLB dan DBE dapat menurunkan frekuensi napas. Kombinasi PLB dan DBE tersebut dapat meningkatkan fungsi paru-paru dan menginduksi pola penapasan yang halus dan lambat.…”
Section: Pembahasan Penerapan Intervensi Kombinasi Plb Dan Dbe Terhad...unclassified
See 1 more Smart Citation
“…Pada kelima pasien mengalami penurunan frekuensi napas setelah diberikan intervensi kombinasi PLB dan DBE. Hal tersebut sejalan dengan penelitian Mulyadi et al (2022) menunjukkan intervensi PLB dan DBE dapat menurunkan frekuensi napas. Kombinasi PLB dan DBE tersebut dapat meningkatkan fungsi paru-paru dan menginduksi pola penapasan yang halus dan lambat.…”
Section: Pembahasan Penerapan Intervensi Kombinasi Plb Dan Dbe Terhad...unclassified
“…Sedangkan kasus IV berusia 47 tahun. Hal tersebut sejalan dengan penelitian Mulyadi et al (2022) yang menunjukkan intervensi PLB dan DBE lebih efektif diterapkan pada responden dewasa awal dan dewasa akhir dibandingkan pada responden lansia. Pada lansia dapat terjadi atrofi otot pernafasan dan penurunan kekuatan otot pernafasan.…”
Section: Pembahasan Penerapan Intervensi Kombinasi Plb Dan Dbe Terhad...unclassified
“…More than three million people died from COPD in 2012, accounting for 6% of all deaths globally. 1,2 The 2018 Basic Health Research (Riskesdas) found that the prevalence of COPD in Indonesia reached 4.5%. It significantly correlated to the incidence of oxidative stress.…”
Section: Chronicmentioning
confidence: 99%
“…Conventional treatment now aims to relieve symptoms, prevent repeated exacerbations, maintain optimal lung function, and improve quality of life. 1,2 According to World Health Statistics, COPD is the third leading cause of death worldwide. Based on data from Basic Health Research (RISKESDAS), COPD has a prevalence of 3.7% per one million population in Indonesia.…”
Section: Introductionmentioning
confidence: 99%